Аналіз електроімпульсних процесів в колах напівпровідних формувачів розрядних імпульсів методом багатопараметричних функцій - Щерба, Анатолій Андрійович; Михайленко, Владислав Володимирович (НТУ "ХПІ", 2014)
У цій статті проведено аналіз електроімпульснихх процесів в електричних колах з напівпровідниковими комутаторами. Створено математичну модель для аналізу перехідних процесів в напівпровідникових перетворювачах установок електроімпульсної обробки різних середовищ. Наведено графіки, що відображають перехідні процеси у електричних колах.

Analysis of the electroipulisnye processes is organized. In this article in electric circuit with semiconductorcommutators. Mathematical model is created for analysis of the connecting processes in semiconductor converter of the installing the electropulsed processing the different ambiences. The Brought graphs, which show the connecting processes in electric circuit. In work is also executed development of the method multivariable modulating function for simplification of the analysis of the connecting processes in electric circuit of the semiconductor shapers radiofrequency class pulse. Use the method muchparametric inflexion functions, which marketed package in прикладном MathCAD, simplifies the analysis of the connecting processes and execution to optimization parameter semiconductor converters, in electric circuit which appear the processes of the charge and category of the capacitive drive to electric powers with variable initial condition. Such approach allows also to do instability mode less in technological load and mode of the consumption to electric powers from network of the energy consumption.
Analysis of the electroipulisnye processes in circuit of the semiconductor shapers charges pulse by method multivariable function
Keywords: електричні кола; напівпровідникові комутатори; перехідні процеси; мережа електроживлення; пакет MathCAD; connecting processes; semiconductor commutators